Detection and epidemiology of bacterial canker (Pseudomonas syringae) on wild cherry (Prunus avium) - Luz, J.P. (1997)
Bacterial canker has been severely affecting wild cherry trees (Prunus avium) and restraining the planting of this valuable hardwood for the last 13 years. The disease has been attributed to the bacterium Pseudomonas syringae pv. morsprunorum, which has caused bacterial canker in sweet cherry since at least the beginning of this century. Twenty-four wild cherry sites were investigated. From eight it was possible to isolate a total of 23 cultures. These were used to test rapid diagnostic techniques in conjunction with 52 other cultures obtained from different sources. Two of the wild cherry cultures were obtained from a nursery, which is of grave concern. The diagnostic techniques tested were based on nutritional tests (Biolog system), nucleic acids (DNA hybridisation probe and REP-PCR), and immunology (slide immunofluorescence and conjugated Staphylococcus aureus agglutination). The Biolog system could identify the bacteria at the species level and allowed a numerical taxonomy study. In this, three clusters were seen, one of P. s. pv. syringae isolates, another of P. s. pv. morsprunorum isolates, and a last one of intermediate isolates, including most of the cultures isolated from wild cherry. These cultures were also intermediate in classical nutritional tests that usually discriminate the two pathovars. It is suggested that the wild cherry cultures are an intermediate form, not yet stabilised. They should be included in the P. syringae pv. syringae rather than in P. s. pv. morsprunorum until more taxonomic work is done. A DNA hybridisation probe obtained from other workers failed to react with some P. s. pv. morsprunorum cultures, possibly because only part of the original probe could be used. Again almost none of the cultures from wild cherry hybridised. Although REP-PCR was too variable to allow identification of P. s. pv. syringae, it could be used to distinguish it from typical P. s. pv. morsprunorum. Again the wild cherry cultures had very different patterns from the ones obtained from P. s. pv. morsprunorum. The immunofluorescence did not have enough specificity to discriminate pathovars or even species but the same antiserum worked well in the conjugated S. aureus agglutination test. The spatial and temporal spread of P. s. pv. morsprunorum replicated in simulated plantations containing single inoculated trees was evaluated. The results suggest that epiphytic forms were ubiquitous and that the spacing between trees was unimportant. One year was enough for a plantation, which was initially free of the bacteria to acquire a population almost equivalent to an inoculated plantation. Single isolates of P. s. pv. morsprunorum, with REP-PCR patterns stable in culture, apparently gave rise to isolates with different patterns within one year of inoculation. The strategy of planting clonal cherry material, supposedly resistant to bacterial canker, can become very risky because of the high phenotypic and genetic variation of P. syringae isolated from wild cherry trees, which was demonstrated by the diagnostic techniques.